KOALA GRAPH THEORY INTERNET SERVICE - TOMASZ GOLUCH; KRZYSZTOF M. OCETKIEWICZ; KRZYSZTOF GIARO (TASK Quarterly, 2015)
KOALA has been created with the idea of C++ library templates, implementing a broad set of procedures in the fields of algorithmic graph theory and network problems in discrete optimization. During the C2 NIWA project, a library has been greatly extended, the code refactored and enclosed with the internet service available in the public repository of the project. Today it contains interconnected educational materials in the form of Wikibook, documentation and sample codes, a multifunctional web-based application for edition of graphs, a collection of over 100 web services which offers a library of selected procedures to be run on the BeesyCluster system.